2002
DOI: 10.21273/jashs.127.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Water Transport through the Sweet Cherry Fruit Surface: V. Conductance for Water Uptake

Abstract: Rain-induced cracking of sweet cherry (Prunus avium L.) fruit is thought to be related to water absorption through the fruit surface. Conductance for water uptake (gtot. uptake) through the fruit surface of `Sam' sweet cherry was studied gravimetrically by monitoring water penetration from a donor solution of deionized water through segments of the outer pericarp into a polyethyleneglycol (PEG) containing receiver solution. Segments consisting of cuticle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…Furthermore, the permeability of cuticular membranes decreased with increasing concentrations of Fe-chelates, leading to the suggestion that Fe-chelates themselves may somehow reduce the size of aqueous pores. A reduction of the water conductance through fruit cuticles after Fe-treatments was also reported by Beyer et al (2002) and Weichert et al (2004). It has been suggested that 100% relative humidity (RH) would be required for a significant cuticular penetration of Fe-chelates, and that addition of hygroscopic humectants would favor foliar uptake (Schö nherr et al 2005).…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, the permeability of cuticular membranes decreased with increasing concentrations of Fe-chelates, leading to the suggestion that Fe-chelates themselves may somehow reduce the size of aqueous pores. A reduction of the water conductance through fruit cuticles after Fe-treatments was also reported by Beyer et al (2002) and Weichert et al (2004). It has been suggested that 100% relative humidity (RH) would be required for a significant cuticular penetration of Fe-chelates, and that addition of hygroscopic humectants would favor foliar uptake (Schö nherr et al 2005).…”
mentioning
confidence: 78%
“…Mechanisms acting during the process of plant cuticular penetration of Fe-compounds include interactions of a variable nature (e.g., electrochemical or osmotic), which may induce the clogging of hydrophilic pathways (Beyer et al 2002;Weichert et al 2004), as supported by the relatively lower penetration rate of more concentrated versus more diluted Fe-containing solutions (Ferná ndez 2004;Schö nherr et al 2005). Consequently, all Fe-compounds were applied in this study at a relatively low concentration (i.e., 2 mM Fe), in contrast to most published Fe spray trials .…”
Section: Discussionmentioning
confidence: 99%
“…WATER PERMEABILITY OF EXOCARP SEGMENTS. Effects of microcracks on the osmotic water permeability coeffi cient (P f ) were determined using the procedure established previously (Beyer and Knoche, 2002). The P f is also referred to as fi ltration permeability or osmotic water permeability P os (House 1974;Schönherr, 1982) or conductance for water uptake g uptake (Beyer and Knoche, 2002).…”
Section: Monitoring Microcracks In Developing Fruitmentioning
confidence: 99%
“…Development of microcracks may be an early event in macroscopic fruit cracking, since 1) the CM is the rate limiting barrier to water transport across the fruit surface (Beyer and Knoche, 2002;Knoche et al, 2000) and water uptake was increased in fruit having microcracks (Glenn and Poovaiah, 1989), and 2) macroscopic cracks were reported to develop along microcracks and progress along their length (Glenn and Poovaiah, 1989).…”
mentioning
confidence: 99%
“…Approved field application rates were: Decis EC 2.5 (containing 25 g l -1 deltamethrin) 200 ml ha -1 , Talstar 8 SC (containing 80 g l -1 bifenthrin) 125 ml ha -1 , Reldan 22 (containing 225 g l -1 chlorpyrifos-methyl) 1500 ml ha -1 . (Beyer & Knoche 2002). The effect of storage duration on LC 50 values was studied by testing whether the slope of a plot of log(LC 50 ) versus time differed significantly from 0.…”
Section: Discussionmentioning
confidence: 99%